"UPGRADING EMOTIONS THROUGH COLORS IN PAINTING": ‘‘चित्रकला में रंगों के माध्यम से भावनाओं का उन्नयन’’ - Verma, Mamta (International Journal of Research -GRANTHAALAYAH, 2014)
Colors have special importance in keeping the emotions alert in the painting. Colors help us in the euphoria of our feelings of happiness, sorrow, excitement, euphoria etc. Colors are helpful in the morphological representation of human emotions. The color is not only the color of the picture, it also expresses the solar heat of the spring, the roaring of the clouds and the fountains of the soil soaked by rain. When the element of color is understood, then black color also fills the light of knowledge. That is why prehistoric humans used mineral colors to engrave their emotions on the rock, in which ocher, ramaraj, coal, chariot and hirauji, etc. are the main colors. In fact, these colors were the basis for the display of prehistoric human expressions. चित्रकला में भावनाओं को सजग रखने में रंगो का विशेष महत्व होता है। रंग हमारे सुख-दुख उत्तेजना, भय, उल्लास आदि सभी भावनाओं के उद्वीपन में सहायक होते है। रंग मनुष्य के मनोभावों के रूपात्मक प्रस्तुतिकरण में सहायक होते है। रंग केवल चित्र की रंगत ही नही है, यह बसन्त के सौरभ को सूर्य के उत्ताप को, मेघों के गर्जन को और वर्षा से भीगी मिट्टी के सौधंे पन को भी व्यंजित करते है। रंग का तत्व जब समझ में आ जाता है तो काला रंग भी ज्ञान का आलोक भर देता है। इसलिये तो प्रागौतिहासिक मानव ने अपने मनोभावो को शिला पर उकेरने के लिए खनिज रंगो का प्रयोग किया जिसमें गेरू, रामरज, कोयला, खड़िया एवं हिरौजी, आदि प्रमुख रंग है। वास्तव में ये रंग प्रागौतिहासिक मानव के भावों के प्रदर्शन का मूलाधार थे।